A 7 year survey of acute hepatitis type B. Issue 12 (December 1983) - Bortolotti, F; Cadrobbi, P; Bertaggia, A; Rude, L; Alberti, A; Realdi, G
Abstract : Epidemiological and clinical features of acute symptomatic hepatitis type B were evaluated in 51 otherwise healthy children and in 13 children receiving immunosuppressive treatment for leukaemia and malignancy, who were admitted to hospital with acute hepatitis B surface antigen (HBsAg) positive hepatitis during a period of 7 years. Blood transfusions, or intimate contacts with asymptomatic HBsAg carriers or with contaminated material during repeated admission to hospital were the possible sources of infection in the immunosuppressed patients, whereas percutaneous exposure was identified as the source in a minority of non-immunosuppressed patients. Features of the acute phase of the illness differed little between the two groups of patients (acute liver failure developed in one patient with leukaemia and in two untreated children). Conversely, chronic evolution was observed in 69% of immunosuppressed patients but in only 9% of untreated children and affected only patients born to HBsAg positive mothers (two of four patients) or patients presenting with papular acrodermatitis (both patients).